2021
DOI: 10.1111/evo.14286
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia and host intrinsic reproductive barriers contribute additively to postmating isolation in spider mites

Abstract: Wolbachia are widespread maternally-inherited bacteria suggested to play a role in arthropod host speciation through induction of cytoplasmic incompatibility, but this hypothesis remains controversial. Most studies addressing Wolbachia-induced incompatibilities concern closely-related populations, which are intrinsically compatible. Here, we used three populations of two genetically differentiated colour forms of the haplodiploid spider mite Tetranychus urticae to dissect the interaction between Wolbachia-indu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(68 citation statements)
references
References 130 publications
5
63
0
Order By: Relevance
“…Morphological classification showed that the Bch line is distinct from T. urticae (electronic supplementary material) and compatible control crosses of T. urticae males of all near-isogenic lines and uninfected Bch females produced hybrid F1 females. Virgin F1 females did not oviposit across our cross types (n= five females per cross type, if present), a post-zygotic reproductive barrier that is commonly observed in interspecific crosses with Tetranychus mites [38,39].…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Morphological classification showed that the Bch line is distinct from T. urticae (electronic supplementary material) and compatible control crosses of T. urticae males of all near-isogenic lines and uninfected Bch females produced hybrid F1 females. Virgin F1 females did not oviposit across our cross types (n= five females per cross type, if present), a post-zygotic reproductive barrier that is commonly observed in interspecific crosses with Tetranychus mites [38,39].…”
Section: Resultsmentioning
confidence: 90%
“…Introgressive transfer of Wolbachia into the Bch nuclear background failed since F1 females did not oviposit. Hybrid sterility is a pervasive post-zygotic reproductive barrier between tetranychid species [38,39]. We morphologically classified the Bch line (electronic supplementary material).…”
Section: Creation and Characterization Of The Tetranychus Nuclear Panelmentioning
confidence: 99%
See 2 more Smart Citations
“…where MD obs and MD c are the estimated MD values in the incompatible and respective compatible crosses (Poinsot et al 1998;Zélé et al 2020;Cruz et al 2021). The corrected FM-CI phenotype (FM corr ) was calculated using the estimated FM values;…”
Section: Phenotypementioning
confidence: 99%